Letramento e polifonia: um estudo de aspectos discursivos do processo de alfabetização - Cecília M. A. Goulart (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
This study seeks to expand the understanding of the notion of literacy by discussing new theoreticalmethodological bases for the pedagogical practice of literacy. This understanding is based on Bakhtins notion of literacy in dialogue with that of polyphony in the context of his theory of enunciation. The concepts of interlocution and of types of discourse also have a relevant role in the study interwoven with theoretical postures of other authors. The discussion evolves from research in which the author has been engaged since 1992 in a state school in the city of Rio de Janeiro, investigating the processes by which children appropriate the written discourse. The article highlights the signs of the presence of the other in texts written by six-year-old children, which reveal the dimension of alterity in the process of constituting written language. The children mix forms of expression as a means of experimenting the tension of senses existing in the use of different strategies and expressive resources and, at the same time, revealing themselves as subjects of and in language. The notion of literacy is posited as an ethical-political horizon for the school.